THE MEANING OF SIGNS IN WI-FI INTERNET ADVERTISEMENT - I Gusti Putu Mahardika Putra; Komang Dian Puspita Candra; I Wayan Juniartha (ID Solutions, 2022)
The researchers are tried to identify the meaning of sign in Wi-Fi Internet advertisement. The data of this study used selected Wi-Fi Internet advertisement from internet. Observation method was conducted in collecting the data through documentation and note-taking technique. The data were analysed qualitatively used theory of meaning proposed by Barthes (1967) and supported theory from Weirzbicka (1996) to identify the meaning of sign in Wi-Fi Internet advertisement. The researchers found two meaning of Wi-Fi Internet Advertisement namely denotative and connotative meaning. The advertiser used denotative and connotative meaning to give information about the product and attract the customer to use the product.